Recent Update on Medicinal Properties of Rotula aquatica Lour. - Biswas, P.; Hasan, I.; Anand, U.; Ghorai, M.; Al-Tawaha, A.R.; Bursal, Ercan; Jain, V. (CRC Press, 2023)
Rotula aquatic Lour., a species of the Boraginaceae family, is a significant medicinal plant in traditional and Ayurvedic medicine and known as Pashanbheda. The plant is a short, branched, woody, and aromatic shrub of about 60-180 cm in height and grows in rheophytic habitats such as in sandy stream beds, over rocks, and pebbles. The plant is mainly distributed in central, middle, and southern India. Mentions of the plant are found in the different traditional medicinal systems for treating kidney stones, bladder stones, vesicle stones, haemorrhoids, venereal diseases, diabetes, and piles and as a diuretic, cardiotonic, laxative, cooling, bitter, and astringent agent. Recent studies confirmed the pharmacological activities of the plant as anti-urolithiatic, hypoglycaemic, anti-inflammatory, antibacterial, and anthelmintic. Though very few experiments have been performed on the plant’s phytochemistry, identified phytochemicals include polyphenols, flavonoids, alkaloids, tannins, quinoline, 3-O-acetyl-11-keto-?-boswellic acid, gallic acid, p-coumaric acid, and vanillic acid, which are important therapeutical agents. More preclinical and clinical trials should be done on the plant to test the traditional claims and discover other potential therapeutic effects. This chapter provides detailed information about the plant, its phytochemistry, and recent studies on its pharmacological activities. © 2024 Taylor & Francis Group, LLC.